2022
DOI: 10.1177/00957984211069058
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Activism Among Black Lesbian, Gay, Bisexual, Transgender, and Queer or Questioning Young Adults: The Roles of Intragroup Marginalization, Identity, and Community

Abstract: Research around the importance of activism for positive development has been primarily focused on a single identity, missing the ways in which race and sexual orientation intersect to influence the communities young adults advocate for. The current study assesses how Black lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) young adults’ experiences of discrimination, identity, and community predict involvement in intersectional activism (e.g., activism for LGBTQ communities of color). With a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Participants' social identities, including race, gender, sexuality, class, and ability, significantly influenced their activism efforts, aligning with research highlighting the influential role of identities in activism engagement [20,34]. Scholars have posited that the significance individuals assign to their social identities shapes their attunement to social injustices and power imbalances in society [54,67]. Identity-based experiences provide a lens through which Black young adults can critically examine social structures, institutions, policies, and practices [25,26].…”
Section: Motivationsmentioning
confidence: 74%
“…Participants' social identities, including race, gender, sexuality, class, and ability, significantly influenced their activism efforts, aligning with research highlighting the influential role of identities in activism engagement [20,34]. Scholars have posited that the significance individuals assign to their social identities shapes their attunement to social injustices and power imbalances in society [54,67]. Identity-based experiences provide a lens through which Black young adults can critically examine social structures, institutions, policies, and practices [25,26].…”
Section: Motivationsmentioning
confidence: 74%
“…Although there is limited research on young Black TGD activists, researchers have found that young Black queer people who report higher levels of community involvement or connection are more likely to engage in Black activism (Pender et al, 2019) and intersectional activism, specifically (Shaheed et al, 2022). Our study adds to this literature by centering young Black TGD individuals and providing potential insights into the reasons why higher levels of community involvement or connection increase the likelihood of engagement in activism for this community.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has found that Black LGBTQ young adults stay connected to the Black community despite feelings of isolation or invisibility. This connection allows Black LGBTQ young adults to receive support when they experience anti-Black racism and helps them foster a sense of collective racial identity that further motivates them to engage in activism (e.g., Ginwright, 2007; Pender et al, 2019; Shaheed et al, 2022).…”
Section: Intersectionality As a Critical Frameworkmentioning
confidence: 99%
“…A consistent finding across this body of research is the importance of community connectedness in identity development and resilience for both Black and TGD people (e.g., Pender et al, 2019; Testa et al, 2014), such as the increased likelihood of engaging in activism within their communities (Wray-Lake, 2019). For example, Shaheed et al (2022) found that Black LGBTQ young adults were more likely to engage in intersectional activism the more they experienced marginalization within LGBTQ communities. Furthermore, research has found that Black LGBTQ young adults stay connected to the Black community despite feelings of isolation or invisibility.…”
Section: Intersectionality As a Critical Frameworkmentioning
confidence: 99%